Analisa Perbandingan Metode MAUT dan Metode TOPSIS Dengan Menggunakan Pembobotan ROC Dalam Sistem Pendukung Keputusan Pemilihan Calon Kepala Desa - Ahmad Rifqi; Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to carry out a comparative analysis process between the MAUT method and the TOPSIS method using ROC weighting. The MAUT method functions to deal with problems in decision making that link several interrelated attributes, in which the method combines the decision maker's preferences for the relevant attributes by giving a weight value to each attribute. Meanwhile, the TOPSIS method is used to select the best alternative from the many choices based on their relative distances from the ideal solution. In this study, weighting using the ROC method is used to objectively determine attribute weight values. The results of the research conducted show that the MAUT Method and the TOPSIS Method with ROC weighting can give good results in determining village heads. The results of the ranking using the MAUT method are A4 with a value of 0.950. while the ranking results using the TOPSIS method are A4 with a value of 0.917.